Pembuatan Pojok UMKM Guna Meningkatkan Eksistensi dan Pemasaran Produk Lokal di Desa Mekarmukti - Alfiaturohmah Alfiaturohmah; Hanifah Hanifah; Muhammad Iqbal; Nur Ratna; Rachma Adelia; Wiji Safitri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Mekarmukti Village MSME Corner is a local initiative that aims to develop the village economy through empowering Micro, Small and Medium Enterprises (MSME). This initiative focuses on increasing production capacity, market access, and improving the quality of local products. This research aims to instill the role of the MSME Corner in supporting the economic growth of Mekarmukti Village, as well as identifying the challenges faced by MSME actors. The research results show that the UMKM Corner makes a significant contribution in creating jobs and increasing the income of village communities. However, there are obstacles such as limited capital, access to technology and marketing that still need to be overcome. With the right support from the government and community, the MSME Corner has great potential to become a driving force for the economy of Mekarmukti Village in the future.